2018
DOI: 10.1002/ece3.4773
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling olfactory and visual information used by field foraging birds

Abstract: Foraging strategies of birds can influence trophic plant–insect networks with impacts on primary plant production. Recent experiments show that some forest insectivorous birds can use herbivore‐induced plant volatiles (HIPVs) to locate herbivore‐infested trees, but it is unclear how birds combine or prioritize visual and olfactory information when making foraging decisions. Here, we investigated attraction of ground‐foraging birds to HIPVs and visible prey in short vegetation on farmland in a series of foragin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Yang, Walther, and Weng (2015) showed that oriental honey buzzards ( Pernis orientalis ) use both visual and olfactory cues when searching pollen doughs in apiaries. Rubene, Leidefors, Ninkovic, Eggers, and Low (2019) found that ground‐foraging birds preferred visual cues over olfactory cues in choice experiments at fields. Potier, Duriez, Célérier, Liegeois, and Bonadonna (2019) tested two scavenging raptor species, Turkey vulture ( Cathartes aura ) and southern caracara ( Caracara plancus ), and showed that they preferred the odor cues of hidden pieces of meat.…”
Section: Discussionmentioning
confidence: 99%
“…Yang, Walther, and Weng (2015) showed that oriental honey buzzards ( Pernis orientalis ) use both visual and olfactory cues when searching pollen doughs in apiaries. Rubene, Leidefors, Ninkovic, Eggers, and Low (2019) found that ground‐foraging birds preferred visual cues over olfactory cues in choice experiments at fields. Potier, Duriez, Célérier, Liegeois, and Bonadonna (2019) tested two scavenging raptor species, Turkey vulture ( Cathartes aura ) and southern caracara ( Caracara plancus ), and showed that they preferred the odor cues of hidden pieces of meat.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of MeSA to contribute to sustainable plant protection has been demonstrated for a number of different pests and crops, and via different mechanisms including attraction of natural enemies (James, 2003;Sasso et al, 2007Sasso et al, , 2009Mallinger et al, 2011;Orre Gordon et al, 2013;Rubene et al, 2019;Byers et al, 2021). Several studies have shown that releasing volatile MeSA in cereal crops can reduce aphid populations (Pettersson et al, 1994;Ninkovic et al, 2003;Prinsloo et al, 2007;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MeSA may have different modes of action that can be exploited for pest management (James, 2003;Ninkovic et al, 2003;Byers et al, 2021). It is attractive to a range of natural enemies of arthropod pests (Mallinger et al, 2011;Orre Gordon et al, 2013) and possibly birds (Rubene et al, 2019), and has shown repellency against aphids (Glinwood and Pettersson, 2000;Prinsloo et al, 2007;Digilio et al, 2012). MeSA is often reported as a plant volatile that is induced by insect feeding, and may play a role in defense signaling within (Heil and Ton, 2008) or between plants (Shulaev et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that HIPVs can attract insectivorous birds [40,42], although a previous study using artificial mixtures of volatiles has not found such an attraction [61]. The positive correlation found between avian the predation rates of artificial larvae and the quantity of emission of volatiles emitted by trees experimentally infested with caterpillars in natural conditions also suggests that olfaction may be the mechanism underlying bird attraction to caterpillar-infested trees [53], although vision may also play an important role in finding prey [42,52,57]. Avian attraction has also been shown in plants treated with methyl jasmonate (MeJA) [41,56], a phytohormone involved in the development of plant defence against herbivory [62][63][64].…”
Section: Introductionmentioning
confidence: 95%
“…In the sea, Procellariiformes and Sphenisciformes can detect dimethyl sulphide (DMS [36,37]), a chemical compound released by phytoplankton when zooplankton and pelagic fishes graze on phytoplankton, thus signaling areas of high productivity in oceans [35,51]. Chemical communication also plays an important role in plant-herbivory-predator interactions in terrestrial systems, as insectivorous birds exploit the chemical indirect cues emitted by plants (Herbivore Induced Plant Volatiles, HIPVs) in response to caterpillar herbivory ( [40,42,[52][53][54][55][56][57], reviewed in [41]). When attacked by herbivorous predators, plants respond in a defensive manner to face such herbivory, including the emission of HIPVs that attract the predators of herbivores [58].…”
Section: Introductionmentioning
confidence: 99%